Refugee and asylum migration to the OECD: A short overview - Timothy J. Hatton (Institute for the Study of Labor (IZA), 2012)
This paper provides an overview of asylum migration from poor strife-prone countries to the OECD since the 1950s. I examine the political and economic factors in source countries that generate refugees and asylum seekers. Particular attention is given to the rising trend of asylum applications up to the 1990s, and the policy backlash that followed. I consider the political economy of restrictive asylum policies, especially in EU countries, as well as the effectiveness of those policies in deterring asylum seekers. The paper concludes with an outline of the assimilation of refugees in host country labour markets.
Keywords: F22; F55; J61; 330; refugees; asylum migration; asylum policy; Flüchtlinge; Migrationspolitik; Asylrecht; OECD-Staaten